An inductorless 1.8 ​mW 2.9 ​dB NF differential LNA integrated to on-chip loop antenna with secondary loop for biomedical applications. (March 2020) - Sunitha, Archana; Manickam, Bhaskar
Abstract: In this paper, a fully integrated inductorless Low Noise Amplifier (LNA) and on-chip antenna for short range biomedical applications are proposed at 2.4 ​GHz. Inductorless configuration eliminates interference with on-chip antenna. A Common-Gate(CG), current re-use, capacitive cross coupled differential LNA provides low power and noise. In the proposed antenna, a secondary loop is formed by attaching the parasitic structure to the main loop antenna, which increases the radiation efficiency and gain of the antenna. The circuit is designed in UMC 65 ​nm technology. LNA and matching network are simulated using Cadence Virtuoso tool and have a gain of 22 ​dB, NF of 2.9 ​dB, IIP3 of −9.21 ​dBm, and return loss −11 ​dB at 2.4 ​GHz. From the Electromagnetic (EM) simulations using Advanced Design System (ADS), the on-chip antenna has a gain of −14dB and efficiency of 1.86%. The proposed design outperforms the state of the art LNAs integrated with on-chip antennas below 15 ​GHz by providing highest gain, lowest power consumption of 1.8 ​mW and longest computed communication range.